Analysis of a new geometric factor for soil resistivity measurement - Andrade, Arthur Francisco (2021)
Grounding is a fundamental part of electrical installations and of the electrical system as a whole. In order to ensure good performance of grounding, it must be properly designed and, for this, a fundamental step is soil-resistivity measurement and stratification. In this sense, this paper compares different procedures for soil modeling from measurements with the four-electrode method. Wenner’s conventional method and a new method, which uses a new geometric factor to estimate with greater accuracy the soil resistivity for the case of small spacings, are compared. For the comparison, finite element method is applied for elaborating case studies. Initially, the performance of both methods is compared for the stratification of a two-layer soil. Then, the differences that the soil modeling methods exert on grounding resistance calculation for the case of simple electrodes (vertical rod and horizontal cable), are analyzed. It is verified that the proposed method provides more accurate results, allowing to model with greater accuracy the resistivity of the soil surface layer. Wenner’s conventional method, if applied with spacing smaller than 1.0 m, resulted in greater than 20% for some of the analyzed cases. With the proposed geometric factor, the maximum error was 2.0%.